IAA concentration of Eleusine Indica seeds as affected by water soaking and refrigeration / Muhamad Aidil Samiran - Samiran, Muhamad Aidil (Faculty of Plantation and Agrotechnology, 2018)
This study focused on determination of indole-3-acetic acid (IAA) in Eleusine indica seeds following water soaking and refrigeration treatment. Standard IAA solutions were used for comparison with the IAA content in the endosperm and husk of the seeds following such treatments. IAA content was found significantly different following the under study treatments. Refrigeration could significantly reduce the IAA content of the endosperm and husk as compared to the control seeds with no water soaking or refrigeration treatment. Water soaking, on the other hand, could only significantly leach out the IAA on the husk while IAA content of the endosperm remained high and comparable to that of the control seeds. The findings were in parallel to the significantly better germination of E. indica seeds following refrigeration treatment in a previous study carried out in the same laboratory. IAA seemed to impose seed dormancy on E. indica seeds.